Mapping Variation in Cellular and Transcriptional Response to 1,25-Dihydroxyvitamin D3 in Peripheral Blood Mononuclear Cells. - Silvia N Kariuki; Joseph C Maranville; Shaneen S Baxter; Choongwon Jeong; Shigeki Nakagome; Cara L Hrusch; David B Witonsky; Anne I Sperling; Anna Di Rienzo (PLoS ONE, 2016)
The active hormonal form of vitamin D, 1,25-dihydroxyvitamin D (1,25D) is an important modulator of the immune system, inhibiting cellular proliferation and regulating transcription of immune response genes. In order to characterize the genetic basis of variation in the immunomodulatory effects of 1,25D, we mapped quantitative traits of 1,25D response at both the cellular and the transcriptional level. We carried out a genome-wide association scan of percent inhibition of cell proliferation (Imax) induced by 1,25D treatment of peripheral blood mononuclear cells from 88 healthy African-American individuals. Two genome-wide significant variants were identified: rs1893662 in a gene desert on chromosome 18 (p = 2.32 x 10-8) and rs6451692 on chromosome 5 (p = 2.55 x 10-8), which may influence the anti-proliferative activity of 1,25D by regulating the expression of nearby genes such as the chemokine gene, CCL28, and the translation initiation gene, PAIP1. We also identified 8 expression quantitative trait loci at a FDR<0.10 for transcriptional response to 1,25D treatment, which include the transcriptional regulator ets variant 3-like (ETV3L) and EH-domain containing 4 (EHD4). In addition, we identified response eQTLs in vitamin D receptor binding sites near genes differentially expressed in response to 1,25D, such as FERM Domain Containing 6 (FRMD6), which plays a critical role in regulating both cell proliferation and apoptosis. Combining information from the GWAS of Imax and the response eQTL mapping enabled identification of putative Imax-associated candidate genes such as PAIP1 and the transcriptional repressor gene ZNF649. Overall, the variants identified in this study are strong candidates for immune traits and diseases linked to vitamin D, such as multiple sclerosis.